Heinriha Skujas privātbibliotēka LU Muzeja Botānikas un mikoloģijas kolekcijās - Kuzņecova, Kristīne (My University, 2019)
Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās Rīgā, Kronvalda bulvārī 4 esošās LU absolventa, biologa algologa Heinriha Skujas (1892–1972) privātbibliotēkas apraksts.

Description of the private library of latvian biologist algologist Heinrich Skuja (1892–1972), a graduate of the University of Latvia. Private library is located in Riga, at the Kronvalda Boulevard 4 in the Botany and Mycology collections of the Museum of the University of Latvia.
Heinrich Skuja's private library in the Botany and Mycology collections of the Museum of the University of Latvia
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; Heinrihs Skuja; Heinrich Skuja; bibliotēka; library; periodiskie izdevumi; periodicals; monogrāfijas; monographs; algoloģija; algology